A METHODOLOGY FOR DEVELOPMENT SYSTEM OPTIMIZATION OF A HYDROCARBON ASSET BASED ON AN INTEGRATED ADAPTIVE GEOLOGICAL MODEL - Murodov Sadriddin Nizomiddinovich, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This  paper  proposes  a  comprehensive  methodology  for  optimizing  the development  system  of  mature  fields  with  high  reservoir  heterogeneity.  The methodology is based on the sequential integration of new geological and technological data  and  hydrodynamic  simulation  results  into  an  updated  three-dimensional  static model. An algorithm for model adaptation to dynamic data is considered, allowing for a  reduction  in  uncertainty  in  the  prediction  of  filtration-capacity  properties.  The implementation of the methodology enables a quantitative assessment of the efficiency of various development scenarios, including changes to the well pattern and operating modes. The result is a justified plan of measures aimed at increasing the oil recovery factor (ORF) and the economic efficiency of the project.